Circular external fixation: the method - Salomone, Carlo; Martínez-Herreros, Isabel; Formica, Matteo; Federici, Marcello; Tornago, Stefano; Antonini, Andrea; Carrega, Giuliana; Riccio, Giovanni (Lo Scalpello - Journal, 2021)
In this study, indications and characteristics of the system are illustrated by using the experience of a reference center for the treatment of osteoarticular diseases with circular external fixation. Deeper insights of the method and the technique of implantation into biomechanics by using circular external fixation will be provided step by step. For simplicity and due to the frequency of system application, we will refer to diaphyseal systems of long bones such as the tibia. Compliance with biological principles as low aggressiveness, mechanical principles as adjustable mechanics with possibility of interaction throughout the whole period of treatment, from exterior to interior of the fixation system, following a safe anatomical path and implantation wire technique, indications in traumatology (high energy, comminuted, open and with loss of substance fractures) and sequelae (non-union, osteomyelitis and deformation) allow a good tolerance of the system and proper achievement of results while minimizing surgical complications and risks 1-3. The use of different instruments, also including newly developed ones, does not alter the fundamental principles of the method.